2022
DOI: 10.1097/wco.0000000000001061
|View full text |Cite
|
Sign up to set email alerts
|

Therapies targeting CGRP signaling for medication overuse headache

Abstract: Purpose of reviewMedication overuse headache (MOH) affects more than 60 million individuals worldwide causing enormous personal and social burden. Only repurposed drugs are available for MOH that share limited evidence for efficacy. The preclinical data suggesting that activation of the calcitonin gene-related peptide (CGRP) pathway is involved in headache chronification along with clinical evidence that monoclonal antibodies targeting CGRP (anti-CGRP mAbs) have good efficacy in preventing chronic migraine, tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 55 publications
0
3
0
1
Order By: Relevance
“…Parece que estos fármacos son igual de eficaces en este grupo de pacientes, reduciendo el consumo de analgésicos por su efecto en la disminución de la frecuencia y de la intensidad de las crisis. Este hecho también se explicaría por el potencial papel del CGRP en la propia fisiopatología de la cefalea por uso excesivo de analgésicos 57 .…”
Section: Pacientes Con Uso Excesivo De Medicaciónunclassified
“…Parece que estos fármacos son igual de eficaces en este grupo de pacientes, reduciendo el consumo de analgésicos por su efecto en la disminución de la frecuencia y de la intensidad de las crisis. Este hecho también se explicaría por el potencial papel del CGRP en la propia fisiopatología de la cefalea por uso excesivo de analgésicos 57 .…”
Section: Pacientes Con Uso Excesivo De Medicaciónunclassified
“…46 Clinical trials assessing the efficacy of antibodies to CGRP or its receptor showed a treatment benefit for patients with MOH. 47 Subsequently, the oral small-molecule CGRP antagonists (gepants) rimegepant and atogepant were also shown to be efficacious in patients with chronic migraine and medication overuse. 48 Ubrogepant may confer a similar benefit, but the efficacy of lasmiditan in patients with MOH is as yet unclear.…”
Section: Key Pointsmentioning
confidence: 99%
“…It is very likely that gepants can also be used in patients with vascular diseases. Gepants might not lead to medication overuse and medication overuse headache (15). The main obstacle for the use of gepants is the very high price.…”
Section: Clinical Implications Acute Migraine Medicationmentioning
confidence: 99%